Brexit: what the draft deal means for science. (22nd November 2018) - Gibney, Elizabeth; Else, Holly
If approved, divorce agreement will see the United Kingdom leave the European nuclear-regulation body — but many uncertainties remain for research. If approved, divorce agreement will see the United Kingdom leave the European nuclear-regulation body — but many uncertainties remain for research.